Enhancing information management through data mining analytics to increase product sales in an e-commerce platform. (6th August 2008) - Kudyba, Stephan; Lawrence, Kenneth
This paper addresses the utilisation of complementary technologies to more effectively identify and accommodate the market demand for product documents available via an e-commerce platform. More specifically, it investigates the utilisation of data mining methodologies to enhance the information management of e-commerce data to better identify consumer purchasing patterns and preferences for engineering-based documents. By enhancing the knowledge of consumer behaviour through the effective transformation of data into actionable information, organisations can enhance the e-commerce functionality to more effectively direct consumers to the existing products that are available within a document repository. The result is a higher volume of sales for existing customer visits and increased customer satisfaction.